Efektvitas Diet Kombinasi Susu Kedelai dan Tepung Kulit Cangkang Kerang Hijau dalam Meningkatkan Panjang Lengkung Rahang - Prameswari, Noengki; Razak, Arifzan; Mulawarmanti, Dian (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
Calcium and magnesium are the important nutrients especially for bone and teeth growth. Cow’s milk has a high calcium, but some people cannot consume it. Soy milk as a cow’s milk alternative has a low calcium, so it might be combined with green mussel shell flour which has a high calcium. To compare diet cow’s milk, soy milk, and combination diet soy milk with green mussel shell flour to increase length of arch. Thirty two 3 weeks old male wistar rats, each weighting between 50-80 grams. This research used post test only control group design. They were randomly divided into 4 groups. K1 group was given aquadest personde 0,0225ml/gBB/day. K2 group was given cow’s milk personde 0,0225ml/gBB/day. K3 group was given soy milk personde 0,0225ml/gBB/day. K4 group was given soy milk personde 0,0225ml/gBB/day with 0,04mg/gBB green mussel shell flour. After 8 weeks, all rats were killed,took their mandible, and and measuredlength of arch by cephalometry analysis. Data was analyzed using one way Anova (p=0,05) showed significant increasing of the length of arch by cephalometry analysis compare to control group.0,00 (p>0,05). Conclusion: Combination of green mussel shell flour with soy milk has proved to increase length of arch by cephalometry analysis in mandible growth.